AIEOP‐BFM consensus guidelines 2016 for flow cytometric immunophenotyping of Pediatric acute lymphoblastic leukemia. Issue 1 (21st February 2017) - Dworzak, Michael N.; Buldini, Barbara; Gaipa, Giuseppe; Ratei, Richard; Hrusak, Ondrej; Luria, Drorit; Rosenthal, Eti; Bourquin, Jean‐Pierre; Sartor, Mary; Schumich, Angela; Karawajew, Leonid; Mejstrikova, Ester; et al.
Abstract : Immunophenotyping by flow cytometry (FCM) is a worldwide mainstay in leukemia diagnostics. For concordant multicentric application, however, a gap exists between available classification systems, technologic standardization, and clinical needs. The AIEOP‐BFM consortium induced an extensive standardization and validation effort between its nine national reference laboratories collaborating in immunophenotyping of pediatric acute lymphoblastic leukemia (ALL). We elaborated common guidelines which take advantage of the possibilities of multi‐color FCM: marker panel requirements, immunological blast gating, in‐sample controls, tri‐partite antigen expression rating (negative vs. weak or strong positive) with capturing of blast cell heterogeneities and subclone formation, refined ALL subclassification, and a dominant lineage assignment algorithm able to distinguish "simple" from bilineal/"complex" mixed phenotype acute leukemia (MPAL) cases, which is essential for choice of treatment. These guidelines are a first step toward necessary inter‐laboratory standardization of pediatric leukemia immunophenotyping for a concordant multicentric application. © 2017 International Clinical Cytometry Society